2010
DOI: 10.1007/s10750-010-0170-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diel changes in fish activity and potential cascading effects in subtropical shallow lakes with different water transparency

Abstract: Fish play a key role in the functioning of shallow lakes. Simultaneously, fish are affected by physical in-lake factors, such as temperature and water transparency, with potential changes in their cascading effects on other communities. Here, we analysed the fish community structure and fish activity in four subtropical shallow lakes, varying in trophic state and water transparency, to assess changes promoted by temperature (i.e. summer and winter) and the light regime (i.e. day and night). We used a passive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…Conversely, long-term effective control of phytoplankton biomass by zooplankton is rarely seen in similar lakes in the subtropics in whole-lake studies with the presence of natural fish communities [39,70,71] and has mainly been reported when fish disappear (e.g., with summer fish kills [33,60]). However, the three-level food web tested displayed the typical trophic cascade effects produced by planktivorous fish, resulting in enhanced phytoplankton biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, long-term effective control of phytoplankton biomass by zooplankton is rarely seen in similar lakes in the subtropics in whole-lake studies with the presence of natural fish communities [39,70,71] and has mainly been reported when fish disappear (e.g., with summer fish kills [33,60]). However, the three-level food web tested displayed the typical trophic cascade effects produced by planktivorous fish, resulting in enhanced phytoplankton biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Planktivorous species were almost equally (species number) found in zones 1 and 3. Fish may affect diversity and water transparency by indirect trophic cascading effects: by consuming zooplankton and plant-attached macroinvertebrate grazers, fish may indirectly enhance phytoplankton and periphyton biomass (Jones and Sayer, 2003;Gelós et al, 2010), thus increasing water turbidity. But in the case of Ehy lagoon (zone 1) low transparency could also be the consequence of the turbulence phenomenon that occurred in this part of the lagoon due to high nutrient loads from both continental drainage and flooding tides (Neves et al, 2011;Konan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…nutrient release, sediment turbation) and biological mechanisms (for example, competition, predation) (Gelós et al, 2010). Fish may affect the spatial distribution of their prey through the behavioural cascades processes (Schmitz et al, 2004;Súarez et al, 2004;Gelós et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of their migratory behavior, the fish species collected were categorized as migratory (between the Yangtze River and Lake Taihu) or resident fishes according to Ni and Zhu (2005) and Ni and Wu (2006). The number of fish captured per month and sampling location was used to calculate the catch per unit effort (CPUE) as Olin et al (2004) andGel os et al (2010).…”
Section: Methodsmentioning
confidence: 99%
“…In terms of their migratory behavior, the fish species collected were categorized as migratory (between the Yangtze River and Lake Taihu) or resident fishes according to Ni and Zhu (2005) and Ni and Wu (2006). The number of fish captured per month and sampling location was used to calculate the catch per unit effort (CPUE) as Olin et al (2004) andGel os et al (2010).To evaluate the fish species diversity, the following indices or equations were used:(i) Index of relative importance (Pinkas 1971;Hyslop 1980):where N D numerical percentage; W D weight percentage; and F D the frequency of occurrence (capture) percentage.(ii) Margalef's richness index (Margalef 1957):where S D total number of species and N D total number of fish samples.(iii) ShannonÀWiener diversity index (Wilhm et al 1968;Krebs 1989):where p i D the proportion of individuals belonging to the ith fish species in the data-set.(iv) Pi elou's evenness index (Pielou 1975):where H 0 D Shannon-Wiener diversity index and S D total number of species. To determine the variation in fish assemblages and environmental conditions and to assess the influence of eutrophication on fish assemblages, the data from the three sampling years, 36 sampling months, and six sample sites were used as replicates of the lake.…”
mentioning
confidence: 99%